THE ONGOING CHARITY OF ORGAN DONATION. CONTEMPORARY ENGLISH SUNNI FATWAS ON ORGAN DONATION AND BLOOD TRANSFUSION - Branden, Stef Van Den (Bioethics, 2011)
Background: Empirical studies in Muslim communities on organ donation and blood transfusion show that Muslim counsellors play an important role in the decision process. Despite the emerging importance of online English Sunni fatwas, these fatwas on organ donation and blood transfusion have hardly been studied, thus creating a gap in our knowledge of contemporary Islamic views on the subject. Method: We analysed 70 English Sunni e-fatwas and subjected them to an in-depth text analysis in order to reveal the key concepts in the Islamic ethical framework regarding organ donation and blood transfusion. Results: All 70 fatwas allow for organ donation and blood transfusion. Autotransplantation is no problem at all if done for medical reasons. Allotransplantation, both from a living and a dead donor, appears to be possible though only in quite restricted ways. Xenotransplantation is less often mentioned but can be allowed in case of necessity. Transplantation in general is seen as an ongoing form of charity. Nearly half of the fatwas allowing blood transfusion do so without mentioning any restriction or problem whatsoever. The other half of the fatwas on transfusion contain the same conditional approval as found in the arguments pro organ transplantation. Conclusion: Our findings are very much in line with the international literature on the subject. We found two new elements: debates on the definition of the moment of death are hardly mentioned in the English Sunni fatwas and organ donation and blood transfusion are presented as an ongoing form of charity.